Pengaruh Bahasa Daerah terhadap Penggunaan Bahasa Indonesia pada Kalangan Mahasiswa - Anita Candra Dewi (P3I Luwu Raya, 2022)
This study aims to examine Description of the vernacular and its influence on student communication patterns. This type of research is quantitative research with regression techniques using tool questionnaires. The research data is sourced from PTP students and the Agricultural Technology Education Study Program. The total sample of 13 people using descriptive Inferential statistical and statistical data analysis techniques. The results showed that local language had a significant effect on student communication patterns.